Quality audit typology and methodology - Pečiulytė, Indrė; Ruževičius, Juozas (Buhalterinės apskaitos teorija ir praktika, 2014)
The methodology of audit is extensively researched both foreign and Lithuanian authors, but there isn’t a full theory of audit, in which is mentioned all the currently existing types of audit. This is due to the quality audit typology and methodology is not fully explored and clearly systematized. Analysing audit concepts it is a challenge to determine which type of audit – performance or management is attributable to the quality audit. The theoretical analysis has shown that in the audit system the quality audit can be assigned as part of the performance audit. Quality audit is important throughout the audit system, as it is part of the evaluation process, which helps auditors to reveal areas for improvement within their organizations. According to the theoretical literature’s systematic analysis and the quality auditors’ questionnaire survey results, in this article the audit system model by the functional character was formed, the advantages and disadvantages of quality audit techniques were identified and recommendations for the quality audit methodology’s improvement were submitted.